Analysis of Basic Education Policies Related to Facilities and Infrastructure - Firman, Firmansah; Ida Bagus Putu Arnyana (International Journal of Contemporary Studies in Education, 2023)
The process of analyzing education policy and providing facilities and infrastructure in educational units lack facillities and infrastructure preparation in the school environment can result in not carrying out the learning process effectively and efficiently. That way, policymakers and stakeholders are expected to be able to think through, describe, and identify the process of preparing facilities and infrastructure carefully to support the continuity of education. This research departs from field observations so as to obtain various solutions. With various sources of factual data as support in compiling scientific work and obtaining data from scientific literature such as journals and reading books using the library research method. The analysis used a qualitative research approach; the technique of collecting data was by observing at school and reviewing the literature. Focusing on the purpose of procuring infrastructure facilities can influence the learning process and the implementation of effective learning, so it is deemed necessary to analyze good educational policies even though there are obstacles and challenges financially. For example, from the results of the learning survey for the 2020–2021 school year, there are around 50% of students whose parents are financially constrained, so they ask for a reduction in school fees. The realization of learning depends on the extent to which schools, through educational policy analysis, describe and identify the facilities and infrastructure that need to be prepared. Government participation is determined by its policies in providing educational facilities.